2010
DOI: 10.1302/0301-620x.92b1.22355
|View full text |Cite
|
Sign up to set email alerts
|

Does the anteromedial or anterolateral approach alter the rate of joint puncture in injection of the ankle?

Abstract: Injection or aspiration of the ankle may be performed through either an anteromedial or an anterolateral approach for diagnostic or therapeutic reasons. We evaluated the success of an intra-articular puncture in relation to its site in 76 ankles from 38 cadavers. Two orthopaedic surgical trainees each injected methylene blue dye into 18 of 38 ankles through an anterolateral approach and into 20 of 38 through an anteromedial. An arthrotomy was then performed to confirm the placement of the dye within the joint.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Palpation-guided tibiotalar joint injections have reported accuracy rates of 67% to 77% in the clinical setting and 78% to 100% in the cadaveric specimens (34,41,43,55,105). Palpation-guided tibiotalar joint injections have reported accuracy rates of 67% to 77% in the clinical setting and 78% to 100% in the cadaveric specimens (34,41,43,55,105).…”
Section: Ankle and Footmentioning
confidence: 99%
“…Palpation-guided tibiotalar joint injections have reported accuracy rates of 67% to 77% in the clinical setting and 78% to 100% in the cadaveric specimens (34,41,43,55,105). Palpation-guided tibiotalar joint injections have reported accuracy rates of 67% to 77% in the clinical setting and 78% to 100% in the cadaveric specimens (34,41,43,55,105).…”
Section: Ankle and Footmentioning
confidence: 99%
“…TT joint USGIs were found to be 100% accurate in three level 2 studies 66 71 80. The mean TT joint LMGI accuracy was 64% in two level 1 studies26 31 and 87% in three level 2 studies 65 66 80. The mean ST joint USGI accuracy of three level 2 studies was 97%,66 71 75 while three level 2 studies reported the accuracy of LMGI to be 89% 66–68.…”
Section: Resultsmentioning
confidence: 94%
“…Seventy-four per cent (17/23) of the studies evaluated injections into a single joint8 63–65 67–70 72–80 and 26% (6/23) assessed injections into multiple joints 16 26 31 52 66 71. Injections into the following joints were evaluated: sternoclavicular (SC; 1/23 (4%)),79 acromioclavicular (AC; 7/23 (30%)),26 63 69 70 72 73 78 elbow (3/23 (13%)),16 26 31 wrist (4/23 (17%)),8 16 26 31 distal radioulnar (DRU; 1/23 (4%)),77 scaphotrapeziotrapezoidal (STT; 1/23 (4%)),74 proximal tibiofibular (TF; 1/23 (4%)),76 tibiotalar (TT; 7/23 (30%)),16 26 31 65 66 71 80 subtalar (ST; 5/23 (22%)),66–68 71 75 and midfoot (1/23 (4%)) 64…”
Section: Resultsmentioning
confidence: 99%
“…This is now a relevant issue for physiotherapists as many working in an extended scope role in the NHS are now performing injections. It has been documented that 14-71% of injections carried out ''blind''-without image guidance-miss their target [23][24][25][26][27]. What we do not know is whether this makes a difference in clinical efficacy.…”
Section: Ultrasound-guided Injectionsmentioning
confidence: 99%